Investigating the dynamics of passenger rolling stock deterioration - Vaičiūnas, Gediminas; Lingaitis, Leonas P. (Transport, 2008)
One of the major economic criteria is associated with the growth of maintenance costs of old rail vehicles. The research aims to determine the ageing criteria of passenger rolling stock, which could take into account fuel, diesel oil and repair costs. Therefore, economic criteria based on the above costs are generated and their comparative analysis is made. The research object is Vilnius locomotive depot. First published online: 27 Oct 2010